Financial Inclusion : Zooming in on Latin America - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2015)
Countries in Latin America and the Caribbean (LAC) have made important strides in promoting financial inclusion of firms and households. However, while the region is broadly at par with its peers on financial inclusion of firms, household inclusion lags behind. Nonetheless, there is substantial heterogeneity across LAC countries. Reducing borrowing costs and strengthening further the regulatory environment, while taking steps to protect efficiency and stability of the financial system, could help close financial inclusion gaps. Reducing financial participation and monitoring costs and relaxing collateral constraints will help spur growth and reduce inequality though trade-offs are likely, as illustrated in the case of Guatemala, El Salvador, and Peru.